Paisagem imaginada e poder religioso: a catedral como espelho - Luiz Felipe Cesar Martins de Brito (2017)
This research paper consists of a study of what has been called an imagined landscape, which means one that is read not only by the analysis of the material and concrete transformations, but also by the observer's gaze, his sensations and imaginaries, as well as by the dominant ideologies that build it. As a case study, this research focused on the landscape configured by two Cathedrals projects idealized for Belo Horizonte, Minas Gerais. The central thesis is that the imagined landscape around these projects has a power of communication as potent as the one that becomes visible in the materiality of the buildings and their surrounding spaces. In order to verify this thesis, some hypotheses were considered: certain buildings can signify objects that emanate certain meanings; such meanings are related to the imaginaries and ideologies referring to a certain social and historical context; the idea of a Cathedral for Belo Horizonte comes from the first decades of the twentieth century; the two projects - the first dated from the 1930s and 1940s, by Clemens Holzmeister, not being built, and the other from the years 2000 and 2010, by Oscar Niemeyer, currently under construction - are architectural and landscape icons to be built in places of visibility in the city. The development of this research carried out a multidisciplinary study of the state of the art in landscape, followed by the study of the two projects for the Cathedral of Christ the King, based mainly on primary sources, many of those still unpublished. The research allowed understanding that both projects consist of architectural and urbanistic icons, based especially on the imaginaries of the various subjects involved in their conceptions, which are capable of expressing the immaterial power of a landscape that wants to communicate a religious domain that intends to be reassumed spatially.